Analysis of the Regional Government Information System of the Republic of Indonesia (SIPD-RI) in the Preparation of the Regional Revenue and Expenditure Budget (APBD) of Badung Regency, Bali Province - Putu Indri Marhaeni Dewi; Ni Putu Tirka Widanti; Nyoman Diah Utari Dewi (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract As a form of transparency and accountability of local governments in preparing the Regional Revenue and Expenditure Budget (APBD) each year, the central government through the Ministry of Home Affairs has launched the Regional Government Information System (SIPD-RI) application. The use of SIPD represents the implementation of one element of e-government, namely e-budgeting. This application is expected to facilitate integration between local and central governments in realizing the vision of “One Data Indonesia.” This study aims to identify and analyze the implementation of SIPD-RI in the preparation of the APBD in Badung Regency. The research method used is qualitative descriptive. Data collection techniques include observation, interviews, documentation, and online data searching. The results of the analysis indicate that the implementation of SIPD-RI in the preparation of the APBD in Badung Regency has generally fulfilled the elements of successful e-government implementation, based on Jane E. Fountain’s theory of e-government development success. However, several challenges remain, including frequent system errors, data inconsistencies, inaccurate report outputs, and limited technical capacity of staff in using the SIPD-RI application and preparing the APBD. Solutions taken include coordinating with the Ministry of Home Affairs, providing consultation channels to address problems, and organizing technical guidance related to SIPD-RI in APBD preparation. Keywords: E-government, SIPD-RI, APBD Preparation